Obstetric violence and the multidisciplinary team - Martins, Isabelle Melo (Seven Editora, 2024)
Obstetric violence is a broad, complex and multifaceted public health problem, which causes economic impacts and morbidity and mortality rates in women, generating many victims with physical and emotional sequelae, often permanent. Currently, there are high rates of obstetric violence in the care sectors for these women. The deficit in the training of health professionals on this topic compromises the reduction of cases of this type of violence. Learning about the recognition, prevention and notification of obstetric violence improves health professionals about obstetric violence. This chapter presents information on the rights of parturients, the identification of obstetric violence, and the prevention of obstetric violence, with the objective of training health professionals about obstetric violence and impacting the perception of obstetric violence, consequently improving the quality of obstetric care. DOI:https://doi.org/10.56238/sevened2024.016-028